2021
DOI: 10.3389/fped.2021.727900
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Acute Poisoning in Hospitalized Children in Southwest China

Abstract: Objective: Acute poisoning in children is characterized by regional differences. This study described the basic situation of childhood poisoning in southwest China based on hospitalized cases.Data and Methods: A total of 1,076 acute poisoning cases among hospitalized children admitted to Children's Hospital of Chongqing Medical University from January 2012 to December 2020 were included in this study. Clinical data such as gender, age, living environment, poisonous substance, and cause of poisoning were statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
8
5
0
1
Order By: Relevance
“…In the current study, most poisoning cases occurred in the 2–3-year-old group, followed by those in the 3–4-year-old group, which is congruent with the results of other studies [22] , [23] . Our findings are consistent with those of a survey from Southwest China that found that the top three age groups for poisoning were early childhood, preschool, and school-age children [10] . Children less than five years of age may have the greatest risk for unintentional paediatric poisoning due to factors such as exploring their surroundings, failing to distinguish between safe and harmful materials, and frequently putting their hands in their mouths.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, most poisoning cases occurred in the 2–3-year-old group, followed by those in the 3–4-year-old group, which is congruent with the results of other studies [22] , [23] . Our findings are consistent with those of a survey from Southwest China that found that the top three age groups for poisoning were early childhood, preschool, and school-age children [10] . Children less than five years of age may have the greatest risk for unintentional paediatric poisoning due to factors such as exploring their surroundings, failing to distinguish between safe and harmful materials, and frequently putting their hands in their mouths.…”
Section: Discussionsupporting
confidence: 91%
“…According to the World Health Organization (WHO), poisoning is one of the top five causes of death due to unintentional injury in children [9] . Despite numerous educational and public health campaigns, poisoning remains the most common medical emergency among children [10] . Children are more vulnerable to serious injuries than adults because of their immature psychological and physical systems, lack of hazard awareness, and poor safety awareness and defence against poisons [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Alhaboob et al (19) demonstrated no gender preponderance for poisoning. Moreover, a male-to-female ratio of 1.2:1 among children (33), with a rising poisoning rate in males by age, has been reported. It is possible that at age < 5 years, both males and females prefer to have similar characteristics and behavioral patterns (13,34).…”
Section: Discussionmentioning
confidence: 99%
“…Poisonings cause significant pediatric morbidity and mortality and economic burdens in the United States and globally, 1,2 corresponding to an increasing burden of disease 3 and increasing youth suicide. [4][5][6] U.S. Poison Centers receive more than 2 million exposure calls annually, over half of which are for pediatric patients.…”
Section: Introductionmentioning
confidence: 99%